2009
DOI: 10.1038/tpj.2009.33
|View full text |Cite
|
Sign up to set email alerts
|

Association of a functional polymorphism in the adrenomedullin gene (ADM) with response to paroxetine

Abstract: To identify genes that may be relevant to the molecular action of antidepressants, we investigated transcriptional changes induced by the selective serotonin reuptake inhibitor paroxetine in a serotonergic cell line. We examined gene expression changes after acute treatment with paroxetine and sought to validate microarray results by quantitative PCR (qPCR). Concordant transcriptional changes were confirmed for 14 genes by qPCR and five of these, including the adrenomedullin gene (Adm), either approached or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…In a luciferase gene reporter assay, constructs containing the A or the C allele of rs11042725 were transiently transfected into RN46A cells (33). Luciferase gene expression was significantly higher under the control of the A allele (associated in our study with higher plasma MR-proADM Table 4-Plasma MR-proADM at baseline by ADM genotype in DIABHYCAR and SURDIAGENE studies Data are means 6 SEM.…”
Section: Discussionmentioning
confidence: 58%
“…In a luciferase gene reporter assay, constructs containing the A or the C allele of rs11042725 were transiently transfected into RN46A cells (33). Luciferase gene expression was significantly higher under the control of the A allele (associated in our study with higher plasma MR-proADM Table 4-Plasma MR-proADM at baseline by ADM genotype in DIABHYCAR and SURDIAGENE studies Data are means 6 SEM.…”
Section: Discussionmentioning
confidence: 58%
“…Genetic variants such as rs11042725 have been reported to have functional effect on the promoter function of ADM (43). The SNP rs4910118 is located at 762 bp downstream of the 3 0 -end of ADM.…”
Section: Discussionmentioning
confidence: 99%
“…This same polymorphism has been associated with predisposition to proteinuria in EH and is found with greater frequency in type II diabetic patients in renal failure compared to controls or diabetic patients without nephropathy [9192]. Specific single nucleotide polymorphisms (SNPs) in AM have also been associated with reduced systolic blood pressure, lower pulse pressure, and reduced urinary sodium excretion in a Chinese population [93], increased risk of developing dysglycemia in a Chinese population [94], and altered response to the antidepressant paroxetine [95]. A particular SNP in the AM receptor gene, CALCRL was found with increased frequency specifically among women with EH in a Japanese population [96], and other studies have found CLR SNPs associated with severe periodontitis [97] and acute primary angle closure glaucoma [98].…”
Section: Adrenomedullin In Pregnancy Complicationsmentioning
confidence: 99%